ANALISIS INFORMASI CITRA ANATOMI MSCT THORAX DENGAN KASUS EFUSI PLEURA KANKER PARU PADA WINDOW MEDIASTINUM POST KONTRAS MENGGUNAKAN VARIASI NILAI WINDOW WIDTH - Tri Puji Hastuti; Yeti Kartikasari; Bagus Abimanyu; Nanang Sulaksono (Poltekkes Kemenkes Semarang, 2020)
Background: Malignancy of lung cancer is the biggest cause of pleural effusion. To diagnose lung cancer pleural effusion, a thorax MSCT can be examined. The MSCT parameter that affects image contrast is window width. The purpose of this study was to determine the differences in the anatomical information of thorax MSCT images in the post contrast mediastinal window to the use of window width range 350-600 HU values in cases of lung cancer pleural effusion, and to determine the appropriate window width value to obtain optimal anatomic image information on Thorax MSCT in cases of lung cancer pleural effusion.Methods: This type of research is quasi experimental. The research was conducted at the Radiology Installation of the Dr. Moewardi Hospital. The data were 60 images of the post contrast mediastinal window thorax MSCT axial slice from 10 patients with 6 window width variations (350 HU, 400 HU, 450 HU, 500 HU, 550 HU, 600 HU). An image assessment was conducted by 3 respondents regarding the resulting of 5 anatomical information. Data analysis used Friedman statistical test.Results: The results showed that there was a difference in the anatomical information of the thorax MSCT in the post contrast mediastinal window to the window width variation in cases of lung cancer pleural effusion with a significance level of p value 0,000 (ρ 0.05). Differences in anatomical image information occur in the anatomy of the aorta, limits of pleural effusion with lesions and clarity of lesions, where as there is no difference in anatomy of the right and left primary bronchus. The optimal use of the window width value for thorax MSCT in the post contrast mediastinal window cases of lung cancer pleural effusion is WW 350 HU with a rank value of 4.61.Conclusions: This study shows that the use of 350 HU window width produces better anatomical image information than the use of other window widths in the case of pleural effusion of lung cancer.